2010
DOI: 10.1016/j.rmed.2009.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Plasma leptin and adiponectin in COPD exacerbations: Associations with inflammatory biomarkers

Abstract: Our data suggest that both leptin and adiponectin are associated with the systemic inflammatory process during exacerbations of COPD. The most significant associations seem to be those with IL-6 and TNF-alpha.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
40
1
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(48 citation statements)
references
References 35 publications
(38 reference statements)
1
40
1
6
Order By: Relevance
“…The design of this study (monthly telephone communication) may not have allowed for objective evaluation of the indications for COPD hospitalisation during follow-up. Our study involved patients with a male:female ratio of ,9:1; however, this was also the case in previous studies by our group with a similar design [39,40], and may reflect the increased prevalence of COPD in males compared with females in Greece [41]. However, the fact that a simple measure of depressive symptoms, such as the BDI, was a significant predictor of clinically important future outcomes in hospitalised COPD patients supports a possible usefulness for this measure in clinical practice.…”
Section: Discussionmentioning
confidence: 87%
“…The design of this study (monthly telephone communication) may not have allowed for objective evaluation of the indications for COPD hospitalisation during follow-up. Our study involved patients with a male:female ratio of ,9:1; however, this was also the case in previous studies by our group with a similar design [39,40], and may reflect the increased prevalence of COPD in males compared with females in Greece [41]. However, the fact that a simple measure of depressive symptoms, such as the BDI, was a significant predictor of clinically important future outcomes in hospitalised COPD patients supports a possible usefulness for this measure in clinical practice.…”
Section: Discussionmentioning
confidence: 87%
“…The serum adiponectin concentration increases during exacerbations, and its elevated levels are observed even 8 weeks after treatment. 35 Behnes et al 36 suggested that adiponectin might play a role in the pathogenesis of systemic inflammatory response during sepsis. 36 An experimental study on cardiomyocytes from neonatal rats showed that hypoxia-reoxygenation-provoked cell death can be attenuated by pretreatment with levels significantly correlated with BMI (R = -0.38; P <0.001), FFM index (R = -0.44; P <0.001) (FIGURE 1AB), total body water (R = -0.49; P <0.001), muscle mass index (R = -0.46; P <0.001), and resting metabolic rate (R = -0.51; P <0.001).…”
mentioning
confidence: 99%
“…Elevation of plasma adiponectin has been found in patients with stable COPD and also during acute exacerbations of COPD (12). Increased plasma adiponectin has been demonstrated in underweight patients with COPD, and adiponectin levels inversely associate with body mass index (BMI), the degree of airflow limitation, and adverse cardiovascular outcomes (13,14).…”
mentioning
confidence: 99%